Coping strategies of Filipino women with breast cancer - Bergado, Felice Ann S.
The productive period of a woman in gestational activities is between 20 years and 35 years. During this period, as the woman reaches the mid-life of adulthood, her physiological functioning is at its optimum. For women, this period has a unique emphasis in that childbearing and reading need provident and nurturant qualities as well as achievement. The immediate family becomes the focus or nurturance.Bombarded with diagnosis of cancer, a woman in this prime age of psychological and economic productivity can have the feeling of having the world switched off on her. The thought of having cancer triggers enormous fears in the woman--fears on the effects of the disease and the uncertainty of treatment outcome on her. Symptoms following the treatment can be as stressful as those caused by the disease. Consequently, interpersonal functioning as well as economic stability are threatened. As these problems occur, the clients engage in coping behaviors in an effort to restore and maintain equilibrium.This study sought to determine the common coping strategies utilized by Filipino women with breast cancer and the factors hypothesized to affect the client's use of the coping strategies.The conceptual framework of this study focuses on three sets of variables:a. personal factors - sociodemographic variables specifically educational status, income level, religiosity, civil status, number of children, social support, personality factors and stage of illness.b. quality of care factors - refer to the information given by the nurses and doctors to the clients, interpersonal relationship, technical competence and follow-up.c. coping strategies - in the domains of spiritual such as prayers and offering self to the will of God; cognitive/psychological such as information seeking, planning, thinking the good side of having the disease, diversion activities, solving the problems, acts of hope, self assurance and safety desires, crying, changing self to become a better person; and social strategies such as talking with family, other people and other women having the same disease, and visiting family and friends.One hundred fourteen participants came from Jose Reyes Memorial Medical Center, East Avenue Medical Center and Lourdes Hospital. These were those who were confined and those who visited the tumor clinics of the three hospitals from August 16, 1996 to September 23, 1996.This study utilized the non-experimental, descriptive survey of opinions with observation. The tools composed of questionnaires, elicited the sociodemographic data and their coping strategies in the forms of checklist and interview schedule on the three sets of variables. The instruments underwent several pilot trials.